Exploring core mental health symptoms among persons living with HIV: A network analysis - Han, Shuyu; Zhang, Yizhu; Yang, Xianxia; Li, Ke; Zhang, Lili; Shao, Ying; Ma, Jianhong; Hu, Yan; Zhu, Zheng; Zhang, Yukun; Wang, Zhiwen (Frontiers in Psychiatry, 2023)
Context Persons living with HIV (PLWH) commonly experience mental health symptoms. However, little is known about the core mental health symptoms and their relationships. Objective This study aimed to evaluate the prevalence of various mental health symptoms and to explore their relationships in symptom networks among PLWH. Methods From April to July 2022, we recruited 518 participants through convenience sampling in Beijing, China, for this cross-sectional study. Forty mental health symptoms, including six dimensions (somatization symptoms, negative affect, cognitive function, interpersonal communication, cognitive processes, and social adaptation), were assessed through paper-based or online questionnaires. Network analysis was performed in Python 3.6.0 to explore the core mental health symptoms and describe the relationships among symptoms and clusters. Results Of the 40 mental health symptoms, the most common symptoms were fatigue (71.2%), trouble remembering things (65.6%), and uncertainty about the future (64.0%). In the single symptom network, sadness was the most central symptom across the three centrality indices (rS = 0.59, rC = 0.61, rB = 0.06), followed by feeling discouraged about the future (rS = 0.51, rC = 0.57, rB = 0.04) and feelings of worthlessness (rS = 0.54, rC = 0.53, rB = 0.05). In the symptom cluster network, negative affect was the most central symptom cluster across the three centrality indices (rS = 1, rC = 1, rB = 0.43). Conclusion Our study provides a new perspective on the role of each mental health symptom among PLWH. To alleviate the mental health symptoms of PLWH to the greatest extent possible and comprehensively improve their mental health, we suggest that psychological professionals pay more attention to pessimistic mood and cognitive processes in PLWH. Interventions that apply positive psychology skills and cognitive behavioral therapy may be necessary components for the mental health care of PLWH.